Analisis Yuridis Batasan Kewajiban Pemberitahuan Informasi (Duty of Disclosure) dalam Pembentukan Polis Asuransi Berdasarkan Undang-Undang Nomor 40 Tahun 2014 tentang Perasuransian - Intan Prima Maharani; Ratna Kumala Hapsarani (Journal of Legal, Political, and Humanistic Inquiry, 2026)
This study examines the juridical boundaries of the duty of disclosure in the formation of insurance policies under Law Number 40 of 2014 concerning Insurance, within the framework of Indonesian insurance law. The research employs a normative legal method using statute and conceptual approaches, focusing on the interpretation of legal norms governing disclosure obligations and their implications for contractual validity. The findings reveal that the existing legal framework, particularly Article 251 of the Indonesian Commercial Code, still reflects a classical approach that places a disproportionate burden on the insured, while modern regulations emphasize consumer protection and transparency. The absence of clear criteria for determining material facts and the extent of disclosure obligations has led to interpretative inconsistencies and increased disputes, particularly in claim rejections and policy cancellations. This study proposes a normative reconstruction by introducing a proportional and reciprocal disclosure framework, supported by a clearer classification of material information and a more balanced sanction mechanism. The research contributes to the development of insurance law by offering a more coherent juridical construction that integrates legal certainty, fairness, and consumer protection within contemporary insurance practices.